Vitamin D3 on Oxidative Stress Markers and Blood Pressure in a UUO Rat Model of Chronic Kidney Disease - Wibowo, Yogo Pardi; Susanto, Agung; Wijaya, Bayu Basuki; Pamungkasari, Eti Poncorini; Pramana, Triyanta Yuli (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Chronic kidney disease (CKD) is a major global health burden, with oxidative stress and hypertension contributing significantly to its progression. Although vitamin D3 is known for its pleiotropic effects, its influence on oxidative stress markers in obstructive nephropathy remains unclear. This study evaluated the effect of vitamin D3 supplementation on blood pressure, malondialdehyde (MDA) levels, and superoxide dismutase (SOD) activity in a rat model of CKD induced by Unilateral Ureteral Obstruction (UUO). In this experimental post-test-only control group study, 30 male white rats (Rattus norvegicus) were randomly assigned to five groups (n = 6 per group) following UUO induction: one control group (placebo) and four treatment groups receiving graded oral doses of vitamin D3 (36, 72, and 108 IU/rat) daily for 14 days. Blood pressure was measured using the tail-cuff method, and serum MDA levels and SOD activity were analyzed at the end of the treatment period. Vitamin D3 supplementation produced significant, dose-dependent improvements in all parameters (p-value < 0,01). Compared with controls, treated groups showed lower blood pressure, reduced MDA levels, and increased SOD activity. The highest dose (108 IU/rat) demonstrated the greatest reduction in oxidative stress and blood pressure. This study aimed to evaluate whether vitamin D3 supplementation ameliorates hypertension and oxidative stress in UUO-induced CKD in rats, supporting its potential as an adjunctive strategy to slow CKD progression. Further studies are required to confirm clinical applicability.